Centralized Load Shedding and Restoration for Future Sustainable Power Systems - De Silva, Marian (My University, 2025)
The evolving modern power systems are integrating increased number of renewable energy sources, these introduced challenges related to frequency stability and system inertia. Traditional underfrequency load shedding schemes which rely on fixed thresholds and decentralized relays, are becoming insufficient in addressing the rapid dynamics of modern smart grids. This thesis investigates the implementation of a centralized Load Shedding and Restoration strategy utilizing the ABB SSC600. Which is an intelligent IED compatible with IEC 61850 and has the possibility to carry out protection and control up to 30 feeders within a medium voltage substation environment. The study involves the design, configuration and testing of LS&R logic using ABB’s PCM600 engineering tool. Two primary scenarios are evaluated under the thesis, a frequency only disturbance caused by a drop in RES generation, and secondly combined frequency and Rate of Change of Frequency event under low-inertia conditions. A five step load shedding strategy is implemented and validated. The results demonstrate that the SSC600 provides accurate and quicker response times. By effectively prioritizing of loads and smooth staged restoration once frequency stability is established
Keywords: electrical power networks; renewable energy sources; smart grids; distribution of electricity; electric substations; fi=Sähkö- ja energiatekniikka|en=Electrical Engineering and Energy Technology|; Master´s Programme in Smart Energy